The role of mothers in anti-corruption education: The development of “BUTIKO” as knowledge-sharing virtual community - Nugroho, Sumarjiyanto B. M.; Susilowati, Indah; Fachrunnisa, Olivia; Prastyadewi, Made Ika; Furoida, Aini Nur (Frontiers in Education, 2022)
This paper contends that if anti-corruption campaigns are to be effective, mothers must be involved in anti-corruption education, especially for children. The process of character-building will require early inculcation of anti-corruption ideals to prevent the manifestation of corrupt behavior in the future. However, lack of access to educational materials, especially in rural areas, makes the role of mothers in educating their children about corruption difficult. In order to overcome this impediment, this paper advances a novel solution based on the use of information technology by mothers to offer anti-corruption education to their children in rural areas. The purpose of this paper is to discuss the proposed framework of Bunda Anti Korupsi ‘Butiko’ (BUTIKO) virtual community. The virtual community helps mothers (Bunda) and children to access character education and anti-corruption knowledge from experts. It is expected that the creation of the virtual community character education will help prevent future corruption.